Pressure controlled drug release in a Zr-cluster-based MOF. Issue 39 (16th September 2016) - Jiang, Ke; Zhang, Ling; Hu, Quan; Zhao, Dian; Xia, Tifeng; Lin, Wenxin; Yang, Yanyu; Cui, Yuanjing; Yang, Yu; Qian, Guodong
Abstract : A Zr-cluster-based MOFZJU-800 was synthesized with high drug loading capacity for controllable drug delivery from 2 days to 8 days. Abstract : A robust zirconium-cluster-based metal–organic framework (MOF)ZJU-800 with an excellent drug loading capacity (about 58.80 wt%) has been synthesized. The system shows an adjustable release time of the drug diclofenac sodium from 2 days to 8 days by controlling the degree of compaction between MOF and drug using pressure.